Purpose, Tasks and Principles of the State Policy in the Field of Combating Cybercrime - A. S. Didenko (Law and Safety)
The extremely rapid development of an information-aware society requires the effective regulation of the state policy in the field of combating cybercrime. The rapid development of technology creates new opportunities in the use of information space, but new opportunities entail new threats in this area. In order to prevent and develop an effective mechanism to repel existing and future threats in the field of cyberspace, it is necessary to study the purpose, tasks and principles of the state policy in the field of combating cybercrime.